White self-criticality beyond anti-racism : how does it feel to be a white problem? - Yancy, George (Philosophy of race., 2015)
"White Self-Criticality beyond Anti-racism powerfully emphasizes the significance of humility, vulnerability, anxiety, questions of complicity, and how being a 'good white' is implicated in racial injustice. This collection sets a new precedent for critical race scholarship and critical whiteness studies to take into consideration what it means specifically to be a white problem rather than simply restrict scholarship to the problem of white privilege and white normative invisibility. Ultimately, the text challenges the contemporary rhetoric of a color-blind or color-evasive world in a discourse that is critically engaging and sophisticated, accessible, and persuasive."--Publisher's description